Julian of Norwich: the influence of late-medieval devotional compilations - Dutton, Elisabeth M. (Boydell & Brewer, 2008)
Compilation and miscellany manuscripts were widely owned in the late middle ages, by both the laity and the clergy. Here, their possible influence on Julian of Norwich's 'Revelations' is explored. The book argues that formal features of compilation are evident in the text, deployed by Julian to give authority and didactic force to the theological debate in which she is engaged. Combining study of compilation manuscripts and manuscripts of the 'Revelations' with structural analysis, it suggests important new ways of reading the 'Revelations', and makes a strong case for compilation as a literary form with creative potential. Dr ELISABETH DUTTON is Senior Research Fellow, Worcester College, University of Oxford.